Microstructure of quasi-one-dimensional superconductor KCr3As3 prepared by K-ion deintercalation. (3rd May 2021) - Zhang, Lu; Li, Jun; Mu, Qingge; Liu, Tong; Yang, Dong; Zhu, Chunhui; Ren, Zhi-an; Tian, Huanfang; Li, Zi-an; Li, Jianqi; Yang, Huaixin
Abstract: The microstructure of quasi-one-dimensional KCr3 As3 (133) superconductors, which were prepared by chemical cation deintercalation from their counterpart K2 Cr3 As3 (233) compounds, are investigated using scanning transmission electron microscopy. The nominal KCr3 As3 crystals generally exhibit irregular nanoscale 133-phase domains accompanied by an amorphous As-deficient phase and cracks as a result of alkali cation deintercalation processes. Analysis of local defective structures reveals the existence of an intermediate state in the transformation from 233 to 133 phase and a possible K-deficient 233-type structure as a nanoscale cluster. Our microscopic investigations offer insight into the microstructure of KCr3 As3 and the alkali metal cation deintercalation processes.